PENCIPTAAN BUKU REFENSI PURA MANDHARA GIRI SEMERU AGUNG GUNA MEMPOPULERKAN WISATA RELIGI KABUPATEN LUMAJANG - Dewi, Nindya Prastitah Shinta; Fianto, Achmad Yanu Alif; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: Media promotion is often considered as the technique of the most effective marketing communication to convey messages to the public. But to be able to arrive at an effective level of promotional media, required some consideration of the elections including the following media promotion. In making this final task, the use of photographic techniques will be presented in a reference book Pura Mandhara Giri Semeru Agung, with the contents of the Visual image message can be designed in more detail, informative, and with a more appropriate size. Pura Mandara Giri Semeru Agung is a religious and cultural attractions that exist in Lumajang. Its existence much sucking attention mostly Hindus, especially in Java and Bali. Even this place is also a temple senior se Asia. This object is able to display the grandeur and unique to Lumajang, so it is worth to be visited and studied. The creation of the reference book is intended as one of the efforts to attract peoples interest to be more interested in visiting the places that have a value of culture and religion in Indonesia, particularly the Lumajang and cultural preservation efforts of Indonesia. By using the technique of photography as supporting information, are expected to provide a complete portrayal of cultural and religious Pura Mandhara Giri Semeru Agung.Â Keywords: Media Promotion, Reference Books, Religious Tourism, Photography